Understanding the influence of melt dripping on UL94 test response in a PA11 system - Seah, Dean G. J. (2023)
A commonly used approach in polyamide systems to achieve a V0 rating in Underwriter Laboratories (UL)-94 test involves the exploitation of melt dripping behavior. That is, not allowing the polymer to completely degrade, and thereby, not creating necessary concentration of volatiles for the flame to sustain on the polymer. However, the governing parameters during this process are yet to be well established and quantified. In this work, some of the parameters that influence this process like the heating rate, melt/flame dripping, frequency and size of drips, molecular weight distribution, and the chemical nature of volatiles are considered. For this purpose, this work revisited the role of melamine cyanurate (MC) in polyamide 11 (PA11) from the viewpoint of UL94 flame test. In contrast to studies on PA6 and PA6,6 with MC that have shown a V0 rating due to enhanced melt dripping, only a V2 rating is achieved in UL94 test even with 20 wt% of MC in PA11. Despite a similar chemical structure, the volatiles emitted during the thermal degradation of these polymers are different and plays an important role in determining the behavior of the sample in UL94 test. Besides, it has been shown that at higher heating rates (as in UL94), the role of MC is primarily limited to dilution in the gas phase as opposed to acceleration in thermal decomposition of PA11 at lower heating rates. The consequence of this behavior is also reflected in the differences in the molecular weight distribution of PA11, its MC formulations, and their melt/flame drips collected during the UL94 tests. Within the framework of the tests carried out in this work, it is also found that mass and size of the drips have no correlation to ratings in a UL94 test. The understanding of these parameters has provided some new insights for building a framework on methodologies for designing polymer formulations for UL94 tests.